O processo de significação da temática “preconceito” no direito e na psicologia: historicidade e estruturação em debate - Falcão, Camila dos Anjos (2020)
Prejudice has been the subject of studies with important academic production. Its conceptualization marks it as a reaction of aversion and / or hostility against a certain individual or group that presents characteristics different from those socially accepted. Thus, there are different ways of understanding prejudice, whether by individual or cultural bias, or by its racial, gender, social aspects, among others. This study aims to outline the concept of prejudice in Brazilian academic productions. Specifically, it seeks to know the researchers, the years of publication of the studies, carry out a geographical and institutional mapping, as well as to identify and analyze the theoretical and methodological aspects of the published productions. To this end, it performs a meta-synthesis of the configuration of the term prejudice in the areas of Psychology and Law in the Catalog of theses and dissertations available on the website of the Coordination for the Improvement of Higher Education Personnel (CAPES). Thus, with the descriptor prejudice, in the Exploration phase, 3,925 publications were obtained, which contain the word “prejudice” in the title, abstract or keywords of the work. In the Refinement phase, the filter “areas of interest: Law and Psychology” was applied, the time frame from 2014 to 2018 and availability of “full document” access, on the Sucupira Platform, which resulted in 220 papers, 43 of which were publications of Law (37 dissertations and six theses) and 177 of Psychology (45 theses and 132 dissertations). Afterwards, with floating reading, the works that, in fact dealt with prejudice and not only used the term in the body of the text, remained: 61 works in the field of Psychology (39 dissertations and 22 theses) and 18 publications in the Law (14 dissertations and 4 theses). In the field of Psychology, all regions are covered with some publication: the States of Paraíba, with 14 works; Ceará, with 10 researches and São Paulo and Sergipe with 7 publications each. Regarding universities, UFPB stands out with 14 works (22.95% of publications). In the area of Law, no studies were found on the subject in the North, despite the presence of Postgraduate Programs. São Paulo (8 publications); Ceará (3) and the other States with only one job each. Regarding publications in the institutions, PUC / SP stands out with three works (16.65% of the surveys). The Description and Interpretation phases generated thematic nuclei of the prejudice typology studied in the Post-Graduation. In the field of Law, the following are analyzed: 'racism', 'migration, peoples and xenophobia', 'prejudice, gender and sexual orientation', 'aesthetic and corporal prejudice', 'stigma and drug addiction' and 'tackling prejudice: legislation and education'. In relation to Psychology, the analysis allows to discuss' racism ',' aesthetic and body prejudice ',' population, migration and xenophobia ',' sexual and gender discrimination ',' prejudice and mental illness' and 'the role of the school institution in fighting prejudice '. The analyzed nuclei indicate an important intersection between the areas of knowledge. The historicity and the structure of prejudiced ideas reaffirm and fossilize, with the force of permanence of values, actions, emotions and thinking. Thus, there are indications of similarities in the two fields, especially in relation to racism and sexual and gender prejudice, being emphasized in 25 (31.65%) and 24 (30.75%) of the studies studied, respectively. It is expected to contribute to debates on production, historical and social, on prejudice in the scientific field, especially in the areas of Psychology and Law, as well as to establish a network of Brazilian researchers. The applicability of this study is directed to the scientific field and to society, in order to generate transformation in the coexistence with marginalized minorities, for not following the imposed social standards, and acting in the context of public policies, in actions with the Government Departments, in the scope of Legal and Education.